Problems of applying incentives in civil law - Yu. I. Chalyi (Bulletin of Kharkiv National University of Internal Affairs)
The article notes that incentives are rarely used in civil law due to both objective and subjective reasons. The objective reason is the peculiarities of the law-regulatory methodology of civil law itself, but they are not an obstacle to the use of incentives in civil law. The specifics of the civil law methodology only determine a certain secondary importance of incentives as legal means of regulating civil relations, but do not exclude the possibility and necessity of their application in general. The subjective reasons are the lack of sufficiently developed general provisions in the civil law doctrine and the lack of provisions of similar content in civil law. Elimination of the latter two subjective obstacles will in the future allow intensifying the use of incentives in the self-regulation of civil relations. Based on the principles of freedom of contract and freedom of unilateral transactions, civil law subjects are free to choose the methods of regulating their relations. This freedom also applies to their choice of incentives as legal means of regulating their individual relations. Increased use of incentives in civil law should be expected primarily in self-regulatory relations.